A Year of Iowa Nature : Discovering Where We Live - Kurtz, Carl (Book collections on Project MUSE., 2014)
Concentrating on Iowa's tallgrass prairie, Kurtz also points his viewfinder toward the great variety of natural habitats in the eastern United States. Arranged chronologically throughout the year, the fifty-five color photos and their accompanying narratives rotate through the seasons like a nature film.